Acoustic Microscopy and Ultrasonic Imaging : From Principles to Advanced Applications. - Maev, Roman Gr (Wiley, 2013)
Novel physical solutions, including new results in the field of adaptive methods and inventive approaches to inverse problems, original concepts based on high harmonic imaging algorithms, intriguing vibro-acoustic imaging and vibro-modulation technique, etc. were successfully introduced and verified in numerous studies of industrial materials and biomaterials in the last few years. Together with the above mentioned traditional academic and practical avenues in ultrasonic imaging research, intriguing scientific discussions have recently surfaced and will hopefully continue to bear fruits in the.